Questions of the actualization economic evaluation of lands - Kovalyshyn, O.; Malakhova, S.; Ryzhok, Z. (Land Management, Cadastre and Land Monitoring, 2018)
The Law "On land evaluation" has approved three types of evaluation: soil rating, economic, monetary, which is divided into normative and expert. Each of them characterizes, according to certain indicators, the quality of the soil and the productivity of agricultural land, determines the value and has its purpose. We want to dwell on the economic evaluation of land, which allows us to assess it from the position of the main means of production in agriculture. The last of its indicators were approved in 1988 and it becomes obvious that they do not meet the current conditions of agriculture and are outdated. Under these conditions, the updating of economic land valuation data becomes relevant.Analysis of recent researches and publications. In their scientific studies Dehtyarenko Yu., Dobryak D., Drapikovsky O., Zayats V., Mantsevich Yu.,Tretyak A., Martin A., Mykula O. and other scholars recognize the need to improve the methodological principles of economic evaluation of agricultural land in modern economic conditions.The purpose of the study is to update the indicators of economic land evaluation in accordance with the results of agricultural enterprises.Results of the researches and their discussion. A comparative assessment in absolute terms (UAH / ha) based on the results of the production of grain crops by agricultural enterprises in the Lviv region for 2015 and the relative values (points) based on the data of the economic appraisal of land in 1988, which makes it possible to detect differences in the economic fertility of the soil are given in Table 1.• 1.                Economic evaluation of arable land by the results of production of grain and leguminous crops by agricultural enterprises in Lviv region for 2015Administrative-territorial areaCost of gross outputPayback costsDifferential incomeUAH/haPnts.UAH/100 UAHPnts.UAH/haPnts.Brody21585,1554169,03674345,1541Busk14251,7855123,2563-1359,2640Horodok10688,383798,6653-3937,4918Drohobych9916,5448118,0762-1421,6834Zhydachiv13815,1443141,7354656,2125Zhovkva9631,8745128,8652-458,7826Zolochiv14322,0956127,5266-839,6543Kamianka-Buzka22269,4652123,3961-2096,0136Mykolayiv11007,5643105,1359-3127,5029Mostyska10792,5940119,2658-1424,6926Peremyshlyany15026,6635141,2547664,4416Pustomyty12385,1253142,5265653,7340Radekhiv20795,0847116,7261-3255,9533Sambir4982,6945174,62571130,4629Skole5184,3430120,6243-617,8212Sokal12073,9454133,6063-126,2539StaryySambir6731,4035104,6454-1953,0221Stryi14646,273969,9757-13612,6025Turka5100,7731134,7846-8,4514Yavoriv6167,7635135,324914,7218Lviv region16604,9547125,3560-1278,5732On the basis of the analysis of residue distribution in the Statistica program, the points of economic land evaluation, which correspond to its actual indicators, which we obtained on the basis of statistical information on the results of production of grain and leguminous crops by agricultural enterprises in the Lviv region for 2015, were calculated (Table 2).• 2.                Results of the economic evaluation for the cultivation of grain and leguminous crops by agricultural enterprises in the Lviv region for 2015Administrative-territorial areaTotal economic evaluation of land, pointsCost of gross outputPayback costsDifferential income198820151988201519882015Brody545367584131Busk554663574028Horodok374353561827Drohobych484262573428Zhydachiv434654572529Zhovkva454252572629Zolochiv564666574328Kamianka-Buzka525461573628Mykolayiv434359562927Mostyska404358572628Peremyshlyany354747571629Pustomyty534465574029Radekhiv475261573327Sambir453757582929Skole303743571229Sokal544463573929StaryySambir353954562128Stryi394657552523Turka313746571429Yavoriv353849571829Lviv region47 60 32 Conclusions and perspectives. In order to update the data of the economic evaluation of land in modern economic conditions, we calculated the differential income, which depends on the yield, costs and prices for the sale of grain crops. As a result of the study, negative differential indices were obtained, which were compared with the 1988 economic appraisal marks and the official statistical data of agricultural production indicators. In order to analyze the data obtained, we create an economic-mathematical model in the form of a regression equation, which reflects the relationship between the points of the economic evaluation of land in 1988 and its actual indicators. However, there is no expected relationship between them. We propose new points for economic land evaluation that reflect the real results of grain and legume production by analyzing the remnants of the correlation-regression analysis.Key words: economic evaluation of lands, differential income, cost of production, selling price, profitability level, correlation-regression analysis, analysis of residues.